Self-reported risk factors for chlamydia: A survey of pharmacy-based emergency contraception consumers - Gudka, S.; Bourdin, A.; Watkins, Kim; Eshghabadi, A.; Everett, A.; Clifford, R. (John Wiley & Sons Ltd, 2014)
Objectives: To investigate the self-reported risk factors for Chlamydia trachomatis in pharmacy-based emergency contraception (EC) consumers, evaluate their pharmacy experience and determine whether they would be willing to accept a chlamydia test from the pharmacy. Methods: A survey for women to complete after their EC consultation was developed from themes identified in a literature search. Nineteen pharmacies in the Perth metropolitan region and 13 pharmacies in rural, regional and remote Western Australia (WA) participated in this study. Key findings: From the 113 surveys completed (n = 75 from Perth metropolitan; n = 38 from rural, regional and remote WA), 85% of respondents were between 16 and 29 years of age and all (100%) of the women had inconsistent barrier contraception. Almost all (94%) of the women had at least two, and nearly half (47%) had at least three out of the four risk factors for chlamydia. Nearly 70% of the women found it very easy/easy to access a pharmacy and felt very comfortable/comfortable discussing EC with the pharmacist. Significantly more women said they would be willing to accept a chlamydia test from a rural, regional and remote WA pharmacy than from a Perth metropolitan pharmacy (P = 0.003). Conclusion: Pharmacy-based EC consumers are at high risk of chlamydia and would be willing to accept a chlamydia test from the pharmacy. There is an urgent need to re-orientate health services in Australia so that all EC consumers, including those obtaining EC from pharmacies, have the opportunity to be tested for chlamydia. © 2013 Royal Pharmaceutical Society.